1986
DOI: 10.1083/jcb.102.6.2234
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression of oncogenes encoding nuclear phosphoproteins but not c-Ha-ras have a relationship to monocytic differentiation of HL 60 cells.

Abstract: Abstract. HL 60 cells were subcloned into variants with different sensitivities to the differentiation-inducing effect of 1,25 dihydroxyvitamin D3 (I,25(OH)2D3), as shown by increased oxidative and phagocytic activity and the appearance of cytoplasmic a-naphthyl butyrate esterase. Brief treatment (4 h) with 1,25(OH)2D3 or 5-azacytidine (5-Aza CR) of sensitive sublines induced monocytic differentiation in a fraction of treated cells. The phenotypic differentiation induced by 1,25(OH)2D3 was preceded by altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 40 publications
(44 reference statements)
1
7
1
Order By: Relevance
“…In contrast, the expression of c-fos became detectable a little later and gradually increased, preceding by a few hr the manifestations of the phenotypic differentiation of these cells (Fig. 31, as reported in more detail in another study (Brelvi and Studzinski, 1986). Specifically, we confirmed the observation of Muller et al (1985) that rapid (< 30 min) induction of c-fos is not detectable following treatment with 1,25(OH)@3.…”
Section: Comparison Of the Rates Of Change In Dna Synthesissupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, the expression of c-fos became detectable a little later and gradually increased, preceding by a few hr the manifestations of the phenotypic differentiation of these cells (Fig. 31, as reported in more detail in another study (Brelvi and Studzinski, 1986). Specifically, we confirmed the observation of Muller et al (1985) that rapid (< 30 min) induction of c-fos is not detectable following treatment with 1,25(OH)@3.…”
Section: Comparison Of the Rates Of Change In Dna Synthesissupporting
confidence: 89%
“…Approximately one third of the cells exposed to this regimen show phenotypic differentiation (shown by, e.g., nonspecific esterase, phagocytosis, morphological changes) which peaks 24-36 hr after exposure to the inducer, and the cells then gradually revert to the undifferentiated phenotype. This transient wave of differentiation was shown to be preceded by a reduced rate of cell proliferation and of c-myc gene expression (Studzinski et al, 1985a), and to be accompanied by an increased expression of the c-fos gene (Brelvi and Studzinski, 1986) but these changes were not previously correlated with the altered rates of DNA synthesis, which is the focus of this study.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, in all these instances and as reported here for CAII mRNA, inhibition of protein synthesis by CHX did not block the effects of 1,25(OH)2D3, indicating that the responses did not necessi-tate the de novo synthesis of other gene products. Instead, we found that it induced an increase in CAII mRNA level, as reported for these other gene products and for differentiationrelated protooncogenes in HL-60 cells (37)(38)(39).…”
Section: Discussioncontrasting
confidence: 42%
“…Indeed, the association between c-Myc downregulation and 1,25(OH) 2 D 3 -induced differentiation of human leukemia cells was one of the earliest findings that initiated the studies of the molecular basis of the cellular changes that follow exposure to this hormone [16,265,309,310]. Subsequently, several studies have shown a marked reduction in c-Myc expression in response to 1,25(OH) 2 D 3 and analog treatment of colon cancer cells [311,312] and prostate cancer cells [268,313], and this was associated with the induction of differentiation [312] and G1 arrest [313].…”
Section: Downregulation Of C-myc Expression In 125(oh) 2 D 3 -Inducementioning
confidence: 99%